The Influence Of Giving Coconut Oil On The Event Diaper Rash In Babies - Marliah; Misrawati (Jurnal Life Birth, 2022)
Naturally processed ingredients that can be considered as an alternative topical therapy that can be used for skin care in babies who experience diaper rash and as a prevention of diaper rash are CO.The purpose of this study was to find the Effect of Coconut Oil Administration on the Incidence of Diaper Rash in Babies in the Work Area of the New Jumpandang Health Center.The research was conducted from January to April 2022 at the Jumpandang Baru Health Center. This research is an experimental study with the design of Two Group Posttest Only Design which aims to find the influence between independent variables and dependent variables. The population in this study was all babies who visited and were at the Jumpandang Baru Health Center as many as 30 people using purposive sampling techniques.The results showed that out of 30 respondents as a sample, it was divided into two groups with 15 people in the intervention group given coconut oil and 15 people in the control group who were not given.The results showed that of the 15 respondents who were sampled in the intervention group, after being given coconut oil, 4 people (37.5%) had diaper rash and 15 people were not given to 13 people who had diaper rash. The results showed that there was an effect of coconut oil administration on the incidence of diaper rash in babies with a value of ρ = 0.001<from α = 0.05.It is necessary for the Puskesmas to plan counseling programs, especially regarding the provision of coconut oil and to midwives to further increase their attention to providing information about the importance of giving coconut oil with diaper rash to babies.